2003
DOI: 10.1177/0950017003017002004
|View full text |Cite
|
Sign up to set email alerts
|

Trolley Dolly or Skilled Emotion Manager? Moving on from Hochschild's Managed Heart

Abstract: This article examines emotion in organizations and the emotion management skills organizational actors possess. While Hochschild's (1983) seminal work on emotional labour is perhaps one of the greatest contributions to our understanding of emotion in organizations, this article challenges key tenets of Hochschild's thesis and goes on to offer an evolved analysis of emotional labour and alternative conceptualizations of organizational emotionality. Using comparable data, this article depicts airline cabin crews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
437
0
18

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 432 publications
(464 citation statements)
references
References 37 publications
(50 reference statements)
9
437
0
18
Order By: Relevance
“…There has already been much written about emotional labour (Hochschild 1983, Bolton and Boyd 2003, Kang 2003 and this literature needs to be incorporated in the conceptualization of body work. Although the concept of 'emotional labour' was initially developed within the commercial service sectors, sociologists of health and illness have also recognised and demonstrated that working, with, for and on bodies in health and social care settings is emotionally draining, laborious and demanding (James, 1989(James, , 1992.…”
Section: Boundaries and Intersectionsmentioning
confidence: 99%
“…There has already been much written about emotional labour (Hochschild 1983, Bolton and Boyd 2003, Kang 2003 and this literature needs to be incorporated in the conceptualization of body work. Although the concept of 'emotional labour' was initially developed within the commercial service sectors, sociologists of health and illness have also recognised and demonstrated that working, with, for and on bodies in health and social care settings is emotionally draining, laborious and demanding (James, 1989(James, , 1992.…”
Section: Boundaries and Intersectionsmentioning
confidence: 99%
“…En se fondant sur le cadre théorique du travail émotionnel développé par Hochschild (1979) à partir des écrits de Goffman (1974), puis affiné notamment par Bolton (2003;2009), la présente étude a pour finalité de cerner les principales causes de l'expression d'émotions (convenues ou de représailles) des télécon-seillers. Cette variable expliquée, conséquence d'un travail émotionnel qui n'est pas effectué ou qui échoue plus ou moins volontairement, a été peu investiguée.…”
Section: Mots-clés : Centre D'appels Téléconseiller Interaction Pounclassified
“…Il s'agirait d'une « marchandisation des sentiments » aliénante pour les employés, aux effets pervers sur leur santé. Bolton et Boyd (2003) nuancent cette présentation, observant que les salariés éprouvent du plaisir à exprimer des sentiments dans leurs relations avec les clients. Ils considèrent qu'Hochschild n'a pas identifié toutes les facettes de la gestion des émotions, parfois instrumentalisées pour des motivations pécuniaires, parfois émises de manière désintéressée ou pour se conformer aux rites d'interaction et aux normes de la profession.…”
Section: Revue De Littérature Et Modèle De Rechercheunclassified
“…The call centre workers described by Callaghan and Thompson (2002) gave freely of their time to late night callers because they felt empathy for them, not because they were told to do so by management (see also Bolton and Boyd 2003). Then too, Bolton's studies of nurses reveal professional and protective feelings to patients and anger or irritation at the increasing bureaucratisation of the health service rather than emotional dupes mindlessly following ‗feeling rules' (Bolton 2005a(Bolton , 2005b.…”
Section: The Changing Nature Of Skillmentioning
confidence: 99%